Financing local development through crowdfunding: An empirical analysis of social projects in Portugal - Bernardino, Susana (2016)
Crowdfunding (CF) is an increasingly attractive source to fund social projects. However, to our best knowledge, the study of CF for social purposes has remained largely unexplored in the literature. This research envisages a detailed examination of the role of CF on the early-stage of the social projects at regional level. By comparing the characteristics of the projects available in the Portuguese Social Stock Exchange (PSSE) platform with others that did not use this source of financial support, we explore its role on regional development. The results we got show that, in most cases, both PSSE and Non-Governmental Organizations projects complemented the services offered by the State or by the private sector. Furthermore, about a quarter of the projects present in PSSE operated in areas that were not being addressed neither by the services offered by the State nor by the ones of the private sector. The results attained show that more recent social ventures have a greater propensity to use PSSE. The same is find in those organizations which work closely with the target audience. We also observed that the use of PSSE was correlated with the geographical scope of the Social Venture. The circumstance of having the social organization acting at a local or regional level seems to be strongly associated with the possibility of using social crowdfunding for financing social projects.